Changes in the frequency and persistence of the Vangengeim-Girs macro-circulation forms in the period 1979–2023 - Jan Degirmendžić (Acta Universitatis Lodziensis. Folia Geographica Physica)
The significantly faster increase in Arctic temperature compared to the global average is causing changes in wind patterns in the mid-latitudes of the upper troposphere. Studies suggest possible changes in the geometry of wind fields, evident in the waviness of geopotential lines or in a series of discrete circulation patterns. This study aligns with the latter research focus. The objective of the analysis is to estimate long-term trends in the Vangengeim-Girs (V-G) macroforms from 1979 to 2023, and since 1999, which is considered a breaking point in the course of Arctic warming.